Perencanaan Dan Perancangan Denpasar Holticulture Vertical Farming, Bali - I Made Bramastya Utama; I Nyoman Gede Maha Putra; Agus Kurniawan (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2021)
Currently, agricultural land in Bali is declining. The western part of Denpasar City is a city with the most densely populated areas and the least agricultural land at present, so it has not been able to meet the food needs of its residents. Therefore, it is necessary to plan vertical agricultural facilities where the vertical method is to save land use. As well as the need to support facilities in the field of economics and education in the form of farmers markets, restaurants and treaning areas. Located at the intersection of Jalan Mahendradatta – Jalan Teuku Umar Barat, Denpasar Barat. By applying the basic concept of sustainable space for agricultural activities and green architectural design themes implemented in the design. By determining the scope of the facility, the community, activities in it, will produce zoning placement, entrance design, mass patterns and shapes appropriate to the needs, efficient flow and circulation design, building facade planning in accordance with the design theme, use of structures appropriate, interior space elements in accordance with the basic concept, outdoor space elements that support the function, and utility systems that are appropriate and required in accordance with the functions and needs of each facility in Denpasar Horticulture Vertical Farming. Considering this, it will produce a design that is right on target.